1991
DOI: 10.1063/1.347695
|View full text |Cite
|
Sign up to set email alerts
|

Carbon doping and lattice contraction of GaAs films grown by conventional molecular beam epitaxy

Abstract: Carbon-doped GaAs films have been grown by solid-source molecular beam epitaxy using a graphite filament. The films were doped from 1×1015 cm−3 to 5×1019 cm−3 and the resulting mobilities are equivalent to beryllium-doped films. A slight dependence of As4/Ga flux ratio on carbon doping was observed. The use of either As2 or As4 did not significantly affect the carbon doping concentrations. Lattice contractions were observed for films doped heavily with carbon or beryllium. For a given doping concentration the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 9 publications
1
16
2
Order By: Relevance
“…It has been well established that for C doped III-V materials beyond the doping level of 1 Â 10 19 /cm 3 , substitutional carbon causes the III-V host lattice to contract due to its small tetrahedral covalent radius (0.77 Å ). Lattice mismatch due to lattice contraction by heavily doped C atom has already been reported and calculated in GaAs, 34,35 GaSb, 36 InGaAs, 37 and AlGaAs 35 material systems. In our case, similar lattice contraction in GaAs 0.35 Sb 0.65 was also observed at the doping level of 5 Â 10 19 /cm 3 .…”
Section: Certification Of Layers Corresponding To Different X-ray Peaksmentioning
confidence: 96%
“…It has been well established that for C doped III-V materials beyond the doping level of 1 Â 10 19 /cm 3 , substitutional carbon causes the III-V host lattice to contract due to its small tetrahedral covalent radius (0.77 Å ). Lattice mismatch due to lattice contraction by heavily doped C atom has already been reported and calculated in GaAs, 34,35 GaSb, 36 InGaAs, 37 and AlGaAs 35 material systems. In our case, similar lattice contraction in GaAs 0.35 Sb 0.65 was also observed at the doping level of 5 Â 10 19 /cm 3 .…”
Section: Certification Of Layers Corresponding To Different X-ray Peaksmentioning
confidence: 96%
“…In the heavily doped sample, the carrier concentration increased slightly for annealing temperatures up to 600°C. At higher temperatures the hole concentration and the mobility both decreased as shown in (Hoke, et al, 1991) …”
Section: Stability Of Carbon Doped Gaas Epitaxial Layersmentioning
confidence: 95%
“…The strain can be measured by X-ray diffraction and several groups have found that the lattice constant is reduced in accordance to Vegard's law. (Hoke, et al, 1991) The results from annealing experiments reported in the literature are tabulated in Table 2.2. Two detailed studies will be highlighted.…”
Section: Stability Of Carbon Doped Gaas Epitaxial Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular we compare the XRD experimental results with the lattice contraction model proposed by W.E.Hoke at al [16]. For sake of completeness we report the lattice contraction formula, which describes a linear increase of the lattice parameter variation in function of the carbon incorporation, that is:…”
mentioning
confidence: 98%